NEXMIF Epilepsy: An Alternative Cause of Progressive Myoclonus. (4th April 2023) - Chorny, Lauren E.; Nordli, Douglas R.; Galan, Fernando
Abstract : An 8-year-old boy with generalized myoclonic epilepsy followed by progressive cognitive decline presented with worsening myoclonus despite being compliant with prescribed clobazam. The movements (Video 1) in conjunction with a worsening cognitive status over time were concerning for a progressive myoclonic epilepsy. Initial EEG captured frequent myoclonic seizures time-locked with spike-wave activity (Figure). Overnight EEG revealed normal sleep architecture. His seizures stopped with valproic acid load. Genetic testing revealed a heterozygous pathogenic variant in NEXMIF (c.2478_2479dup), which is associated with NEXMIF encephalopathy. NEXMIF encephalopathy is characterized by mild to severe intellectual disability and includes myoclonic seizures, absence seizures, and atonic seizures. 1